Publishing Death. Symbols, Religious Themes, and Individualisation in Death Notices in the Swedish Daily Newspapers (1945) 1976 - 1995_2 - Dahlgren, Curt (Lund University, 2014)
The present study analyses 6,699 death notices appearing in Swedish newspapers from 1976 through 1995, and 5,766 death notices in specifically urban newspapers from the same period. The death notices are analysed using the same method as in an earlier study by theologian Per Block (Lund University), making it possible to study changes in the use of text in death notices already from 1945.

The analysis shows that the number of cross symbols decreased markedly, from nearly 100 % of the death notices in 1976 to 39 % of the notices generally in 1995, and to 32 % of the notices in urban newspapers, while the number of alternative symbols increased. Interviews showed that a recurring concern was to choose a symbol that in some way portrayed the identity of the deceased. This may reflect an increased individualism and a reaction against the anonymity perceived in the cross symbol, which for many indicated only that somebody had died.

The text portion of death notices has changed in that the number of notices containing language associated with Christianity decreased from 1945 to 1995. An attempt was made to relate these changes in death notices to changes in the rate of church oriented religiosity, but no clear connection was found.

This study was part of a larger project, Cultural indicators: The Swedish Symbol System 1945-1975-1995 (KUSS II), funded by the former Research Council for the Humanities and Social Sciences.

Purpose:

The aim of the project was to study the contents of death notices in Swedish newspapers; how death notices are designed today (in the 1990s) and how they have changed over time. These issues were related to questions of secularisation and individualisation in Swedish society.

The dataset consists of a sample of 5767 death notices published in Swedish city newspapers during the years 1976-1995. The data includes the actual text from the death notices as well as coded data describing the level of religious content, symbols used, the size and political affiliation of the newspaper, etc. The data can be retrieved in MS Excel or SPSS format.

Projektet syftade till att undersöka hur dödsannonser utformas idag samt hur de förändrats över tid. Underlaget utgörs av drygt 13 000 dödsannonser från åren 1976 - 1995, varav 6699 annonser utgörs av ett urval från svenska dagstidningar och 5767 annonser utgörs av ett urval från storstadstidningar. Då detta material är bearbetat på samma sätt som gjorts i en tidigare undersökning av Per Block (Lunds universitet) kan förändringarna i dödsannonsernas texter studeras från och med 1945.

Fram till slutet av 1970-talet var korset den näst intill allenarådande symbolen för döden. Studien visar att de efterlevande under 1990-talet istället hade en önskan om att både dödsannonsens symbol och text ska förmedla något om den avlidnas personlighet. Mellan 1976 och 1995 minskade därför förekomsten av kors som symbol i dödsannonser från nära 100 % under 1976 till 39 % i det allmänna urvalet 1995 och 32 % i storstadsurvalet, medan andra symboler ökade i antal. Detta kan tyda på en ökad individualisering och en reaktion mot den anonymitet som man upplevt att korset förmedlat, genom att endast vara en symbol för att någon har avlidit.

Dödsannonsernas texter har förändrats genom att annonser innehållande text med ett kristet språkbruk minskat i antal mellan 1945 och 1995. Ett försök gjordes att relatera detta till förändringar i den kyrkliga religiositeten i samhället, men ingen tydlig koppling hittades.

Detta projekt utgjorde ett delprojekt i ett annat HSFR-projekt, "Kulturindikatorer: svensk symbolmiljö 1945-1975-1995 (KUSS II)".

Syfte:

Projektet syftade till att undersöka hur dödsannonser utformats under 1990-talet samt hur de förändrats över tid, i relation till samhällets sekularisering och individualisering.

Datasetet utgör ett urval av 5767 dödsannonser publicerade under åren 1976-1995 i svenska storstadstidningar. Texten i dödsannonserna är utskriven i klartext medan använda symboler, bedömning av dödsannonsernas religiösa innehåll, uppgift om sörjande samt om tidningens upplagestorlek och politiska färg är kodad data. Materialet finns tillgängligt i Excel- eller SPSS-format.
Att offentliggöra döden. Symboler, religiösa temata och individualisering i svenska dagspressens dödsannonser (1945) 1976 - 1995_2
Keywords: religious beliefs; religiös tro; religious affiliation; religiös tillhörighet; individualism; individualism; religious behaviour; religiöst beteende; obituary; dödsannons; secularisation; sekularisering; Social behaviour and attitudes; Socialt beteende och attityder; Religion and values; Religion och värderingar; Sociology; Sociologi; Religious Studies; Religionsvetenskap; Ethnology; Etnologi